The Impact of Colors on Learning - Bo Chang; Renmei Xu; Tiffany Watt (Adult Education Research Conference, 2018)
The purpose of this review paper is to find out how colors can impact leaners’ learning by manipulating their cognition and emotions.
Keywords: Colors; memory; cognition; emotion